A Diverse Library of Chiral Cyclopropane Scaffolds via Chemoenzymatic Assembly and Diversification of Cyclopropyl Ketones - Donggeon Nam (10036518); Viktoria Steck (3915986); Robert J. Potenzino (10036521); Rudi Fasan (1307055) (2021)
Chiral cyclopropane rings are key pharmacophores in pharmaceuticals and bioactive natural products, making libraries of these building blocks a valuable resource for drug discovery and development campaigns. Here, we report the development of a chemoenzymatic strategy for the stereoselective assembly and structural diversification of cyclopropyl ketones, a highly versatile yet underexploited class of functionalized cyclopropanes. An engineered variant of sperm whale myoglobin is shown to enable the highly diastereo- and enantioselective construction of these molecules via olefin cyclopropanation in the presence of a diazoketone carbene donor reagent. This biocatalyst offers a remarkably broad substrate scope, catalyzing this reaction with high stereoselectivity across a variety of vinylarene substrates as well as a range of different α-aryl and α-alkyl diazoketone derivatives. Chemical transformation of these enzymatic products enables further diversification of these molecules to yield a collection of structurally diverse cyclopropane-containing scaffolds in enantiopure form, including core motifs found in drugs and natural products as well as novel structures. This work illustrates the power of combining abiological biocatalysis with chemoenzymatic synthesis for generating collections of optically active scaffolds of high value for medicinal chemistry and drug discovery.